THE BABYNSKA SUITE TUFFS OF THE CONTINENTAL FLOOD BASALTS OF WESTERN VOLYN: MINERALOGY, PETROGRAPHY, PETROCHEMISTRY, GENETIC AND APPLIED SIGNIFICANCE - Бацевич, Н.В.; Наумко, І.М.; Федоришин, Ю.І. (Institute of Geological Sciences, NAS of Ukraine, 2024)
According to the data of comprehensive precision research, the spatial distribution and mineral composition were revealed, the petrographic and petrochemical features, and the genetic and practical significance of the Babynska effusive-pyroclastic suite tuffs of the continental flood basalts of Western Volyn were clarified in connection with the copper content. The thicknesses and hypsometry of the relief of the paleosurface of the pyroclastic formations of the Babynska suite were analyzed and the important elements of its vertical and lateral structure (by area) were clarified, the real picture of which is reflected in the constructed maps of the thicknesses and relief of the paleosurface of the pyroclastic formations of the suite, in particular, on the Ratnе–-Kamin-Kashyrsk Area. The formation of the Babynska suite tuffs in the regime of gravitational deposition of pyroclastic material with the accumulation of tuff deposits at the stage of incomplete solidification of volcanic material and the formation of coarse, non-rhythmic layering, without clear signs of redeposition, i.e. of volcanomictіс origin, has been proven. Differences in the mineral composition and petrochemistry of tuffs of different colors: gray-green and red-brown were found. Emphasis is placed on the enrichment of native copper in tuffs of gray-green color and possible explanations for this correlation are proposed. The obtained results from a genetic point of view provide important information for paleovolcanogenic and paleogeographical reconstructions, in practical terms they contribute to the improvement of the copper bearing prospects of volcanogenic layers of the continental flood basalts and can be proposed for use by production organizations of the geological profile.